2014
DOI: 10.3233/cbm-140424
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of putative cancer stem cell marker CD44 in different histological subtypes of lung cancer

Abstract: CD44 could be a valuable tool for the study of lung CSCs and provide a novel therapeutic target for treatment of the patients with lung cancer in combination with conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The latters display several stem cell-associated properties including self-renewal capability, higher clonogenic potential, resistance to chemotherapy and the expression of diverse CSCs markers, such as CD133, ALDH1 (detected as ALDH activity), Nanog and CD44. Noteworthy, none of analyzed markers showed a high and consistent expression in all the spheroids patient-derived LCSC lines, that were used in this study, thus confirming the heterogeneity in lung CSCs marker expression [46][47][48]. Our results show that CPTH6 preferentially inhibits cell viability and activates the apoptotic program of spheroid LCSCs with properties of CSCs.…”
Section: Discussionsupporting
confidence: 60%
“…The latters display several stem cell-associated properties including self-renewal capability, higher clonogenic potential, resistance to chemotherapy and the expression of diverse CSCs markers, such as CD133, ALDH1 (detected as ALDH activity), Nanog and CD44. Noteworthy, none of analyzed markers showed a high and consistent expression in all the spheroids patient-derived LCSC lines, that were used in this study, thus confirming the heterogeneity in lung CSCs marker expression [46][47][48]. Our results show that CPTH6 preferentially inhibits cell viability and activates the apoptotic program of spheroid LCSCs with properties of CSCs.…”
Section: Discussionsupporting
confidence: 60%
“…cd44 is commonly considered to be a cancer stem cell marker and it is found overexpressed in lung cancer tissues especially in lung cancer stem cells. High expression of CD44 in lung cancer tissue was significantly correlated with poor prognosis of NSCLC patients (24). A previous finding showed that the absence of CD44 in lung cancer cells could result in suppression of cancer stem cell properties including downregulation of tumor occurrence and reversing multi-drug resistance (25).…”
Section: Discussionmentioning
confidence: 87%
“…In a combined group of pulmonary and gastrointestinal neuroendocrine neoplasms originally described as carcinoids, the patients with lymph node or distant metastasis lacked CD44 in the tumours significantly more frequently [85]. Thus, the prognostic role of CD44 expression in NENs is different from the negative findings in many carcinomas, including pancreatic ductal adenocarcinoma, gastric adenocarcinoma, clear cell renal carcinoma or non-small cell lung carcinoma, among others [11,[86][87][88]. In our study, there also was no association between CD44 and such morphological parameters, such as high grade and stage, which are indicative of a poor prognosis.…”
Section: Cd44mentioning
confidence: 99%